Sosialisasi Intervensi Non-Farmakologi Untuk Dismenore Primer bagi Remaja Putri di Wilayah Kerja Klinik Esti Husada Kota Semarang - Wibowo, Syifa Sofia; Belladiena, Alfiena Nisa (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to provide knowledge for adolescent girls about overcoming primary dysmenorrhea with non-pharmacological interventions to improve women’s reproductive health status. The method of implementing this service uses health education-based socialization. The evaluation instrument for this activity uses a pre-test and post-test, which is then analyzed descriptively by comparing the average value between the two tests. The results of this service activity show an increase in the average value between the pre-test and post-test, which shows an increase in adolescent girls’ knowledge about overcoming primary dysmenorrhea with non-pharmacological interventions. Through this activity, it is expected to improve the reproductive health status of adolescent girls, namely preventing the onset of further diseases or sequelae due to primary dysmenorrhea.